Konstruksi Sosial Penambang Marmer Mengenai Lingkungan IMIT di Kabupaten Tulungagung - Ayuni, Fitri; Jannah, Raudlatul (Laboratorium Sosiologi FISIP Universitas Jember, 2020)
This research is motivated by managing the natural resources of the people living in the Tulungagung Indonesian Marble Industry environment (IMIT). IMIT mining causes water, soil, and air pollution. The relationship between IMIT and the surrounding community formed the social construction of the IMIT process, which was rejected, accepted, and even now can be established cooperation. Communities living in the IMIT environment can survive by utilizing waste that pollutes the environment or as a marble miner. The knowledge possessed by the community towards the environment influences social actions. This study aims to describe and analyze the social construction of marble miners in the climate